The Ellipsis of the Controversy. The Political, Media and Digital Logics in the TikTok Account of the Head of Government of the City of Buenos Aires (2020-2023) (Andamios, Revista de Investigación Social, 2025)
The aim of this paper is to investigate the mediatization of politics in TikTok in the contemporary era, taking into account the modes of enunciation of an Argentinean ruler in his official account, and comparing the period of the Covid-19 pandemic, the immediate aftermath and the 2023 presidential campaign. Using methodological tools from socio-semiotics and theories of the mediatization of politics, we analysed the type of meaning-producing social operations present in Horacio Rodríguez Larreta’s account during the period in which he was Head of Government of the City of Buenos Aires. The conclusion was to show the combination of political, ludic, electoral, social network and media logics in the different moments analysed between 2020 and 2023, as well as the existence of a new type of digital militant subject of TikTok.
Keywords: TikTok; mediatization; political; government; discourses